Treatment burden in glomerular diseases: advances and challenges in immunosuppressive therapy - Shankar, Mythri; Lamech, Tanuj Moses (Frontiers in Nephrology, 2025)
Glomerular diseases represent a significant global health challenge, complicated by the intricate management required for their treatment. We examine the treatment burden associated with the immunosuppressive therapies used to manage these conditions, focusing on the efficacy, side effects, and financial implications of commonly used medications such as glucocorticoids, mycophenolate mofetil (MMF), cyclophosphamide, calcineurin inhibitors and Rituximab. Immunosuppressive treatments, while effective in controlling disease activity, can result in a variety of adverse effects ranging from gastrointestinal symptoms and bone marrow suppression to increased infection risks, necessitating careful monitoring and dose adjustments to mitigate these risks. Hence, the need for a balanced approach in therapy management, incorporating regular monitoring and potential dose modifications to enhance patient outcomes while minimizing side effects. Additionally, these treatments have an economic impact, particularly in lower-income regions where access to medication and the cost of medication can limit patient outcomes. There have been certain advancements in treatment modalities, such as the use of enteric-coated formulations and tailored dosing schedules, which aim to improve drug tolerability and adherence. By addressing these critical aspects, we aim to shed light on the ongoing challenges and developments in the management of glomerular diseases, emphasizing the need for continued research and innovation in therapeutic strategies to reduce the overall treatment burden and improve the quality of life for affected individuals.